2020
DOI: 10.1007/s13202-020-00956-8
|View full text |Cite
|
Sign up to set email alerts
|

Beneficiation of Nigerian bentonite using local materials

Abstract: In previous studies, it has been found that the Nigerian bentonite is deficient in terms of its fluid loss and rheological properties which includes yield point. Also, due to its high calcium content and low sodium content as opposed to foreign bentonite, it does not meet the API standard of drilling. This research was carried out to beneficiate the Nigerian bentonite as regards its fluid loss properties, rheological properties and wellbore stability. Snail shell is seen as waste substance in Nigeria, and Mucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Studies on beneficiating our local bentonite to see if they can compare with the imported bentonite have been suggested by researchers [10, 12,]. Among the recent studies on beneficiation of Nigeriabentonites using local materials are [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on beneficiating our local bentonite to see if they can compare with the imported bentonite have been suggested by researchers [10, 12,]. Among the recent studies on beneficiation of Nigeriabentonites using local materials are [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded from their result that the rheological properties of Ishiagu local clay can be improve and be a good substitute for the foreign imported bentonite when beneficiated with soda ash, potassium chloride and Pac R at their right concentration. Greatest percentage of bentonite used within Nigeria are imported due to the deficiency of the local clays in rheological and fluid loss properties [17] but studies has shown that imported bentonite-local clay blend in the right proportion could save Nigeria 12 to 36% of the cost of bentonite clay used to drill wells in the country [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They include suitable surface chemistry, chemical inertness, mechanical resistance, high surface area, optimum porosity and ultimately thermal stability. Mucuna solannie contains high percentage of carbon as shown by scanning electron microscope image (Igwilo et al 2020), hence, is expected to exhibit these characteristics. Thermal stability of the material has been highlighted in the same material and other previous works.…”
Section: Problem Statementmentioning
confidence: 99%
“…Also, it is used as an additive for the formation of drilling mud since it contains sizeable quantity of sodium and calcium molecules [16]. Experimentation using Mucuna solannie, periwinkle and snail shell as additives to Nigerian bentonite [12], [13] also proves that suitable fraction of nanoparticles and inhibitive ions that are very essential in the stability of wellbore effectiveness and fluid loss control are found in them. The sizes of nanoparticle range less than 100nm shows new or enhanced properties that depend on sizes in relation to the particle of large size having the same material [17].…”
Section: Introductionmentioning
confidence: 95%
“…Drilling fluids and their additives are used so as to increase the life span of drilling equipment and reduce the cost of drilling the oil and gas well [11]. The beneficiation of Nigerian bentonite using local materials such as periwinkle, snail shell and Mucuna solannie, according to previous research, has discovered that in order to beneficiate the rheological characteristics of drilling fluids, Mucuna solannie has the ability to do so in the presence of calcium to sodium base composition [12,13]. Bentonite is the major substance that is used to enhance viscosity and provide the control of fluid loss in a drilling mud.…”
Section: Introductionmentioning
confidence: 99%